PERAN STRATEGI GENERASI Z DALAM OPTIMALISASI PEMANFAATAN TEKNOLOGI DIGITAL TERHADAP PELAKU UMKM DI KABUPATEN DELI SERDANG - Feberlina Hulu; M. Chaerul Rizky; Dewi Nurmasari Pane; Dea Putri Ananda; Larissa Pia Revianty (Berajah Journal, 2026)
This study aims to identify and analyze the role of Generation Z strategies in optimizing the utilization of digital technology among Micro, Small, and Medium Enterprises (MSMEs) in Deli Serdang Regency. Amid the rapid advancement of the digital era, digital transformation has become a crucial necessity for MSMEs to enhance their competitiveness, expand market reach, and improve operational effectiveness and efficiency. However, many MSME owners still face various challenges in utilizing digital technology optimally, including limited digital literacy, financial constraints, and a lack of understanding of digital marketing strategies. This research employed a quantitative approach using a survey method involving 65 MSME respondents. The data were analyzed through reliability testing, descriptive statistics, multiple linear regression, F-tests, and t-tests using IBM SPSS software. The results indicate that all research instruments met the reliability criteria, with Cronbach’s Alpha values exceeding 0.70, confirming that the instruments were reliable and suitable for data collection. The simultaneous test results revealed that Generation Z strategies collectively have a significant effect on the optimization of digital technology utilization among MSMEs. Meanwhile, the partial test results showed that the Generation Z Strategic Role variable (X1) has a positive and significant effect on the optimization of digital technology utilization among MSMEs, while the other variables did not demonstrate a significant influence. The findings suggest that Generation Z holds a strategic position as an agent of change in supporting the digital transformation of MSMEs. Their contributions are reflected in the utilization of social media as a promotional tool, the implementation of digital marketing strategies, the enhancement of digital literacy, and assistance in adopting various technologies that support business activities. Therefore, stronger collaboration and synergy among Generation Z, government institutions, higher education institutions, and MSME actors are essential to accelerate sustainable digital transformation and improve the competitiveness of MSMEs in the digital economy era.